Remote Teaching in Professor Training: Three Latin American Experiences in Times of COVID-19 Pandemic - Orlando Fernández Aquino; Patricia Medina Zuta; Eldis Román Cao (MDPI AG, 2021)
The subject matter has been based on three systematizations of experiences in teacher training through remote teaching, during the COVID-19 pandemic of 2020-2021. They were developed in IES in Brazil, Ecuador, and Peru. The objective has been to show the experiences implemented to build the teachers' pedagogical knowledge, from online teaching practices. The theoretical framework has been the theory of collaborative and developmental learning, according to L. S. Vigotski and his followers. The work methodology has been the systematization of experiences, according to Jara and others. The results of the Brazilian experience show how it is possible for students of the degree in pedagogy to acquire didactic knowledge and develop skills, through collaborative work in virtual rooms. The Ecuadorian experience shows the effectiveness of teaching focused on autonomous work, which is based on asynchronous activities. The results of the experience in Peru show how asynchronous accompaniment is an effective means for guidance and sustained feedback by the trainer, with an impact on the process of construction of a scientific text and on the productivity of the doctoral student in Education.